2023
DOI: 10.1021/acs.jpcb.2c07699
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Grafted Hybrid Diblock Copolymer Brush (GO-graft-PEG6k-block-P(MA-POSS)) as Nanofillers for Enhanced Lithium Ion Conductivity of PEO-Based Nanocomposite Solid Polymer Electrolytes

Abstract: Nanocomposite solid polymer electrolytes (NSPEs) with PEO as the matrix and (i) GO or (ii) GO-graft-PEG 6k or (iii) GO-graft-PEG 6k -block-P(MA-POSS) as nanofillers have been fabricated to elucidate the impact of the filler morphology on the lithium ion conductivity. GO-graft-PEG 6k was obtained by grafting PEG 6k onto GO via esterification. GO-graft-PEG 6k -block-P(MA-POSS) was prepared via surface-initiated atom transfer radical polymerization. Fourier-transform infrared spectroscopy revealed enhanced salt d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…As functional polymers for polymer-based solid-state electrolytes, polyethylene oxide (PEO) looks more attractive due to the tendency to form a stable complex with alkali metal salts, which can provide a higher ionic conductivity. Meanwhile, PEO’s excellent electrolyte affinity and moderate swelling rate make it an outstanding gel polymer electrolyte that could lower the interfacial resistance between the electrode and electrolyte, providing better rate performance. Yet, these aliphatic polymers, like polyolefin components, still lack thermal and mechanical stabilities, which seriously hampers their practical applications at an elevated temperature. ,, To overcome the defective ionic conductivity along with the safety issues under a high working temperature of the commercial polyolefin separators, coating a heat-labile but ionic conductive PEO polymer layer onto a heat-resistant and sturdy framework seems an effective way to obtain high-performance batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…As functional polymers for polymer-based solid-state electrolytes, polyethylene oxide (PEO) looks more attractive due to the tendency to form a stable complex with alkali metal salts, which can provide a higher ionic conductivity. Meanwhile, PEO’s excellent electrolyte affinity and moderate swelling rate make it an outstanding gel polymer electrolyte that could lower the interfacial resistance between the electrode and electrolyte, providing better rate performance. Yet, these aliphatic polymers, like polyolefin components, still lack thermal and mechanical stabilities, which seriously hampers their practical applications at an elevated temperature. ,, To overcome the defective ionic conductivity along with the safety issues under a high working temperature of the commercial polyolefin separators, coating a heat-labile but ionic conductive PEO polymer layer onto a heat-resistant and sturdy framework seems an effective way to obtain high-performance batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of the co‐authors of this paper reported the NSPEs with PEO as the matrix and GO‐ graft ‐PEG‐ block ‐P(MA‐POSS) as the nanofiller. [ 39 ] A significant enhancement in ion conductivity was observed as compared with the PEO/GO‐ graft ‐PEG‐based NSPEs. Based on the reported literature, it can be stated that GO, due to its unique 2D structure and oxygen‐containing polar functional groups, has got a great potential as nanofiller in the design of NSPEs for high‐performance Li‐ion batteries.…”
Section: Introductionmentioning
confidence: 99%